BIOGENIC SYNTHESIS OF SILVER NANOPARTICLES USING TRACHYSTEMON ORIENTALIS L. AND THEIR ANTIBACTERIAL ACTIVITIES - Çelebioğlu, Hasan Ufuk; İmamoğlu, Rizvan; Taş, Recep; İmamoğlu, Rizvan; Taş, Recep; Çelebioğlu, Hasan Ufuk (TANGER Ltd., 2021)
Nanotechnology is a scientific field for the characterization, production, and application of nanoscale particles of 1-100 nm size. Due to their large surface area and small size, nanoparticles have different properties compared to bulk materials such as mechanical, electrical, magnetic, and chemical properties. They can be synthesized by physical, chemical and biological methods. The biosynthesis of nanoparticles is the synthesis of nanoparticles using microorganisms or plants with biomedical applications. This synthesis approach stands out as a cost-effective, environmentally friendly, bio-compatible, safe, and green approach. The present study aims to synthesize silver nanoparticles by green chemistry using Trachystemon orientalis L. extract and to investigate anti-bacterial and anti-fungal effects properties. UV–Visible absorption, fourier-transform infrared spectroscopy, and scanning electron microscopy analyses confirmed the synthesis. The results showed that silver nanoparticles have inhibitory effect on both gram-negative (E. coli, Klebsiella pneumonia and Pseudomonas aeruginosa) and gram-positive (Staphylococcus aureus and Enterococcus faecalis) bacterial strains. Furthermore, they showed anti-fungal activities against Candida utilis and Candida albicans. Silver nanoparticles can affect the cell walls of the microorganism, changing the structure of cell membranes and even causing cell death. They can also increase the permeability of cell membranes, generate reactive oxygen species, and interrupt the replication of deoxyribonucleic acid. In conclusion, green synthesis of silver nanoparticles using Trachystemon orientalis L. extract can be an effective method for biomedical purposes. © 2022 Elsevier B.V., All rights reserved.
13th International Conference on Nanomaterials - Research and Application, NANOCON 2021 -- Brno; Orea Congress Hotel Brno -- 177511
Keywords: Antibacterial; Antifungal; Nanoparticle; Silver; Trachystemon Orientalis L